An Energy Efficient MAC Protocol for Wireless Ad-Hoc Networks - P K, Shafna (IJRDO -Journal of Computer Science Engineering, 2015)
-Wireless networks become an integral part of the modern communication infrastructure, Energy-efficiency is an important design consideration due to the characteristics of wireless ad hoc network, particularly for mobile users with limited power supply. Medium access control (MAC) protocols play an important role in providing a fair and efficient allocation of the available bandwidth. A new energy-efficient MAC protocol (e-MAC) is proposed in this paper. In the proposed scheme, the packet transmission is adjusted based on network load. Thus nodes need to wake up only at the assigned time and in remaining time they enter into sleep state. There by reduces the energy consumption. Thus proposed scheme achieves high throughput, low packet transmission delay.